1969
DOI: 10.1017/s0033583500001190
|View full text |Cite
|
Sign up to set email alerts
|

Control of muscle contraction

Abstract: As is well known, the memorable discovery of Galvani (1791) was followed by the development of two new fields of science, electrochemistry and electrophysiology. During the course of this development, the most remarkable feature of the original finding, i.e. ‘contraction of muscle induced by a piece of metal’, gradually came to be ignored. As a consequence, the simple question as to how electrical stimulation might induce muscle contraction was left unanswered until the middle of this century, when several phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
319
3
4

Year Published

1972
1972
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 765 publications
(333 citation statements)
references
References 60 publications
7
319
3
4
Order By: Relevance
“…Ferritin particles were found preponderantly on the cytoplasmic surface of the membrane, in agreement with published data showing an asymmetry of the Ca 21 + Mg t+ -ATPase within the sarcoplasmic reticulum membrane . Comparison of the density of ferritin particles in fast and slow myofibers suggested that the density of the Ca 2+ + Mg t+ -ATPase in the sarcoplasmic reticulum membrane in a fast myofiber is approximately two times higher than in a slow myofiber .The sarcoplasmic reticulum is the intracellular membrane system of skeletal muscle that controls sarcoplasmic Ca" concentrations, thereby regulating the contraction-relaxation cycle (4,11,28) . It creates a separate membranous compartment in muscle cells that surrounds each myofibril like a fenestrated sleeve (8,10,21) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ferritin particles were found preponderantly on the cytoplasmic surface of the membrane, in agreement with published data showing an asymmetry of the Ca 21 + Mg t+ -ATPase within the sarcoplasmic reticulum membrane . Comparison of the density of ferritin particles in fast and slow myofibers suggested that the density of the Ca 2+ + Mg t+ -ATPase in the sarcoplasmic reticulum membrane in a fast myofiber is approximately two times higher than in a slow myofiber .The sarcoplasmic reticulum is the intracellular membrane system of skeletal muscle that controls sarcoplasmic Ca" concentrations, thereby regulating the contraction-relaxation cycle (4,11,28) . It creates a separate membranous compartment in muscle cells that surrounds each myofibril like a fenestrated sleeve (8,10,21) .…”
mentioning
confidence: 99%
“…The sarcoplasmic reticulum is the intracellular membrane system of skeletal muscle that controls sarcoplasmic Ca" concentrations, thereby regulating the contraction-relaxation cycle (4,11,28) . It creates a separate membranous compartment in muscle cells that surrounds each myofibril like a fenestrated sleeve (8,10,21) .…”
mentioning
confidence: 99%
“…It has been proved that caffeine releases Ca ions from the sarcoplasmic retic-ulum(SR) (WEBER and HERZ,1968;EBASHI et al,1969).But the tension even at 16mM caffeine is not maintained but decays spontaneously.The result suggests that Ca-release from SR is interrupted (CHIARANDINI et al,1970b),although Cauptake by SR is preserved.Neither Ca-release induced by caffeine nor Ca-uptake is affected by membrane hyperpolarization,at least so effectively as to modify the time course of contraction.Although it has been reported that potassium contracture is modified by caffeine (L,UTTGAU and OETLIKER,1968;CAPUTO,1976),the action of caffeine on SR must be electroneutral and independent of membrane potential change.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that caffeine at a concentration greater than about 5mM produces a sustained contracture (SANDOW,1965).Recently, however, several authors reported oscillatory or repetitive contractions evoked by caffeine in intact frog skeletal muscle (CONWAY and SAKAI,1960;MARCO and NASTUK,1968;GAU and OETLIKER, 1968), in the skinned fiber of frog skeletal muscle et al,1969;ENDO,1970;FORD and PODOLSKY,1972;NATORI,1972),and in intact crayfish muscle (CHIARANDINI et al,1970a;ZACHAR,1971).The repetitive caffeine contractions will be caused by the cyclic increase and decrease in sarcoplasmic free Ca ion concentration (ENDO,1970(ENDO, ,1975.Therefore,studies of these contractions will give an explanation of Ca release and Ca uptake processes.They will also provide us with some evidence on the mechanism of intracellular propagation of the contraction. and then gradually decreased (Fig.1,C).If caffeine concentration was 2-4mM,the muscle developed the tension accompanied with two to four peaks (Fig.1,A,B,D).…”
mentioning
confidence: 99%
“…Furthermore, though there was no significant difference between the heart weight of the two groups, histological findings revealed marked necrosis and fibrosis of myocardiac tissue. With regard to cardiac movement, the driving force is derived from the interaction among myocardiac myosin, actin and ATP [5], with the interaction between troponin and tropomyosin regulating the myocardiac contraction [4]. On the other hand, CK is essential to myocardiac contraction for supplement of ATP and is measured as a variable marker enzyme in myocardiac disorder [3,9].…”
mentioning
confidence: 99%